In vitro study of larvacidal effect of Chrysomya bezziana between atsiri oil (Piper betle leaf) from Sri Lanka and Bogor - April H Wardhana; S Muharsini; S Santosa; L.S.R Arambewela; S.P.W Kumarasinghe (Jurnal Ilmu Ternak dan Veteriner, 2010)
Treatment of myiasis caused by the larvae of Chrysomya bezziana resulted variation results. The aim of the experiment are to compare larvacidal effect of atsiri oil of Piper betle leaf originated from Sri Lanka and Bogor agains Chrysomya bezziana larvae and to identify atsiri oil using Thin Layer Chromatography (TLC).  Silica gel plate GF254 with toluena and ethyl ecetate as diluents was used in TLC. L1 and L2 of Chrysomya bezziana larvae were used for in vitro assay using agar plate contained atsiri oil of three concentrations ie. 2, 3 and 4%. Asuntol 1% and aquadest sterile were used as positive and negative control, respectively. Ten larvae were used in five replicates. The larvae were observed every 30 minutes for four hours. Larval mortality were counted and probit analysed using POLO-PC software, therefore the lethal concentration (LC50 and LC95) and lethal time (LT50 and LT95) were defined. The results showed there was a difference on migration distance between atsiri oil from Sri Lanka and Bogor on nRf 79-88 analysed using TLC. In vitro assay showed that both lethal concentration and lethal time of atsiri oil from Sri Lanka was higher than from Bogor. This results indicated that larvacidal effect of atsiri oil from Bogor was stronger than atsiri oil from Sri Lanka in in vitro both on L1 and L2. Key Words: Piper Bitle Leaf, Atsiri Oil, Chrysomya bezziana, Sri Lanka, Bogor